Family Empowerment Based on Mambosuri Cultural Values to Support Exclusive Breastfeeding in the Gunung Tinggi Primary Health Care Area: Pemberdayaan Keluarga Berbasis Budaya Mambosuri dalam Mendukung ASI Eksklusif di Wilayah Kerja Puskesmas Gunung Tinggi - Anna Waris Nainggolan; Imarina Tarigan; Muhammad Riezky; Siti Nurmawan Sinaga; Esra E Sinaga; Cesy Marlianata Simanullang (Room of Civil Society Development, 2026)
Low exclusive breastfeeding coverage remains closely linked to limited family support and sociocultural influences in infant feeding decisions. In Batak communities, strong kinship structures position the extended family as a key decision-making unit during pregnancy and early childcare. This community engagement program employed a participatory family-based intervention using a one-group pretest–posttest design to empower families to support exclusive breastfeeding through a culturally grounded Mambosuri approach in the Gunung Tinggi Primary Health Care area. The program involved 32 third-trimester pregnant women and their families over a three-month period. The intervention integrated cultural reflection sessions, interactive family discussions, written commitment development, and pre–post evaluation of family knowledge. Findings showed a significant increase in mean knowledge scores from 62.4 to 84.7 (p < 0.001), as well as an increase in the proportion of the good comprehension category from 37.5% to 81.2%. The most notable improvement was observed in fathers’ perceived roles in breastfeeding support. However, the short duration of assistance and the absence of a control group limit broader generalization of the findings. These results suggest that integrating local cultural values into family-centered education may strengthen collective readiness for exclusive breastfeeding in similar community contexts.